Determinants of the sustained employment of physician assistants in hospitals: a qualitative study - Timmermans, Marijke J.C.; Vught, Anneke J. A. H. van; Maassen, Irma T. H. M.; Draaijer, Lisette; Hoofwijk, Anton G. M.; Spanier, Marcel; Unen, Wijnand van; Wensing, Michel; Laurant, Miranda G. H. (BMJ open, 2016)
Objectives To identify determinants of the initial employment of physician assistants (PAs) for inpatient care as well as of the sustainability of their employment. - Design We conducted a qualitative study with semistructured interviews with care providers. Interviews continued until data saturation was achieved. All interviews were transcribed verbatim. A framework approach was used for data analysis. Codes were sorted by the themes, bringing similar concepts together. - Setting This study was conducted between June 2014 and May 2015 within 11 different hospital wards in the Netherlands. The wards varied in medical speciality, as well as in hospital type and the organisational model for inpatient care. - Participants Participant included staff physicians, residents, PAs and nurses. - Results The following themes emerged to be important for the initial employment of PAs and the sustainability of their employment: the innovation, individual factors, professional interactions, incentives and resources, capacity for organisational change and social, political and legal factors. - Conclusions 10 years after the introduction of PAs, there was little discussion among the adopters about the added value of PAs, but organisational and financial uncertainties played an important role in the decision to employ and continue employment of PAs. Barriers to employ and continue PA employment were mostly a consequence of locally arranged restrictions by hospital management and staff physicians, as barriers regarding national laws, PA education and competencies seemed absent.